HUBUNGAN QUALITY OF NURSING WORK LIFE DENGAN STRES KERJA di Ruang Rawat Inap RSU HGA Depok - Vera Septiana (2020)
Occupational stress on susceptible nurses is often the case in the workplace that makes a problem in the service and performance of nurses. The Quality of work life of nurses who can get insight into how it works better to sustain a nurse's workforce. The purpose of this research is to know the relationship of quality of life nurse working with work stress in inpatient room RSU HGA Depok, benefit from this research as a recommendation in academic developing which is particularly in the field of nursing management, the design of this research is analytical descriptive analysis with cross-section, samples amounting to 50 people, sampling using Total sampling techniques, statistical test results showed that there is a significant the job Quality nurse life with stress work with P-0 023 value. The research is expected to balance QNWL in terms of working contexts such as supervision, communicating with other health workers in improving quality by lowering working pressure.